Influence of Electric Potential on Dielectric Barrier Discharge (DBD) Cold Plasma Treatment and Its Effect on the Affinity of Leaf Printing on Cotton Fabric - Seelarat, Weerasak; Porjai, Porramain; Phasuk, Sasamol; Nilsang, Poonyanuch (Trends in Sciences, 2025)
This research aimed to develop a fabric printing process that utilizes natural dyes in combination with dielectric barrier discharge (DBD) plasma treatment. The study focused on determining the optimal electric potential for plasma treatment of cotton fabric and implementing eco-printing by transferring leaf pigments onto the fabric through heat transfer. Four types of leaves used for cotton fabric printing include Teak leaves (Tectona grandis Linn. f.), Indian trumpet flower leaves (Oroxylum indicum L. Kurz), Castor Bean leaves (Ricinus communis L.), and Bellyache bush leaves (Jatropha gossypifolia L.). Cotton fabric was subjected to DBD cold plasma treatment at 500, 1,000, 1,500, and 2,000 V, respectively, prior to leaf printing. The highest absorption coefficient and scattering coefficient (K/S) values were obtained from each printed leaf. The results revealed that high-voltage plasma treatment leads to a high K/S. These findings confirm that cold plasma has altered the physical structure of the cotton fibers, facilitating improved dye penetration into the fabric. Scanning Electron Microscope (SEM) images showed that untreated cotton fibers appeared smooth, round, and undamaged, while plasma-treated fibers exhibited rough, flattened, and fractured surfaces. However, the results concerning color fastness properties, including rub, light, and wash fastness, indicated that the color tends to fade and wash out easily. The optimal electrical potential for plasma treatment was 1,000 V, resulting in the cotton fibers absorbing the highest color intensity. This voltage also maintained favorable mechanical characteristics, with warp and weft tensile strengths of 500 and 360 N, respectively, and elongation values of 15.4 and 17.6%. HIGHLIGHTS Dielectric Barrier Discharge (DBD) Plasma enhances surface properties without damaging the material’s core structure and is an environmentally friendly process. The use of (DBD) Plasma with Eco Print is an innovative approach that enhances fabric properties, improving its ability to absorb plant-based dyes more effectively. The selection of the appropriate electric potential (Voltage) for using DBD Plasma with cotton fabric. GRAPHICAL ABSTRACT